Business Risk Management Planning at Public Accounting Firm in Batam City - Andy Lau; Wisnu Yuwono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This research was conducted to find out the business risk management plan at the Public Accounting Firm in Batam City and can take action to prevent for minimize the risks. This study uses a descriptive contextual approach to analysis and data collection techniques in this study are interviews. Respondents who were interviewed must have knowledge and competence in related fields so that the data obtained can reflect the actual conditions. The results of this study indicate that there are 5 risks in the Public Accounting Firm in Batam City which include 4 medium risks and 1 low risk. Most of the risks that occur are caused by a lack of audit planning. Therefore, the Public Accountant Office in Batam City needs to implement a more effective and efficient audit plan to be able to prevent and minimize the risks that will occur.